Association Between Antenatal Antimicrobial Therapy and Autism Spectrum Disorder—A Nested Case-Control Study - Abelson, Nitzan; Meiri, Gal; Solomon, Shirley; Flusser, Hagit; Michaelovski, Analya; Dinstein, Ilan; Menashe, Idan (Frontiers in Psychiatry, 2021)
Background: Multiple prenatal factors have been associated with autism spectrum disorder (ASD) risk. However, current data about the association between antimicrobial use during pregnancy and ASD is limited. Methods: A nested matched case-control study of children with ASD (cases), and children without ASD or other psychiatric or genetic disorders (controls). We compared the use of antimicrobial therapy during the three months before conception or during pregnancy between mothers of cases and controls and used multivariate conditional logistic regression models to assess the independent association between maternal use of antimicrobials during pregnancy and the risk of ASD in their offspring. Results: More than half of the mothers in the study (54.1%) used antimicrobial drugs during the three months before conception or during pregnancy. Rates of antimicrobial use were lower for mothers of children with ASD compared to mothers of controls (49.0% vs. 55.1%, respectively; p=0.02), especially during the third trimester of pregnancy (18.8% vs 22.9%respectively; p=0.03), and for the use of penicillins (15.7% vs. 19.7%, respectively; p=0.06). These case–control differences suggest that antimicrobial administration during pregnancy was associated with a reduced risk of ASD in the offspring (aOR=0.75, 95% CI=0.61-0.92). Interestingly, this association was seen only among Jewish but not for the Bedouin mothers (aOR=0.62, 95% CI=0.48-0.79 and aOR=1.21, 95% CI=0.82-1.79). Conclusions: The reduced risk of ASD associated with prenatal antimicrobials use only in the Jewish population suggest the involvement of other ethnic differences in healthcare services utilization in this association.